Решите х+2=5х-2(х-3) 4(x+8)-7(x-1)=12 3(x-2)-5(x+3)=27 5x-2(x-4=9x+23 6x-3(x-1)=2+5x

shonchak shonchak    3   22.05.2019 16:20    0

Ответы
х+2=5х-2(х-3)
х+2=5х-2х+6
-2x=4
x=-2

4(x+8)-7(x-1)=12
4x+32-7x+7=12
-3x=-27
x=9

3(x-2)-5(x+3)=27
3x-6-5x-15=27
-2x=48
x=-24

5x-2(x-4)=9x+23
5x-2x+8=9x+23
-6x=15
x=-2.5

6x-3(x-1)=2+5x
6x-3x+3=2+5x
-2x=-1
x=0.5
ПОКАЗАТЬ ОТВЕТЫ
Дарьяпоможет Дарьяпоможет  18.06.2020 04:32
х+2=5х-2(х-3) x+2=5x-2x+6  x+2=5x+6   4x=-4 x=-1

4(x+8)-7(x-1)=12 4x+32-7x+7=12  3x=27 x=3

3(x-2)-5(x+3)=27 3x-6-5x-15=27  2x=-48 x=-24

5x-2(x-4)=9x+23  5x-2x+8=9x+23  6x=-15 x=-2,5

6x-3(x-1)=2+5x  6x-3x+3=2+5x  1=2x  x=1/2
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика